Experimental Investigation of Dynamic Response and Deformation of Aluminium Honeycomb Sandwich Panels Subjected to Underwater Impulsive Loads - Da-Lin Xiang; Ji-Li Rong; Xuan He (Shock and Vibration)
The response of aluminium sandwich panels with three thicknesses’ core subjected to different underwater loading levels has been studied in the fluid-structure interaction (FSI) experiments. The transient response of the panels is measured using a three-dimensional (3D) Digital Image Correlation (DIC) system, along with high-speed photography. The full-field shape and displacement profiles of dry face sheets were recorded in real time compared with those of monolithic plate. The out-of-plane deflection and in-plane strain were quantified and analyzed. Three typical deformation modes of sandwich panel were identified. The results show that the core structure is crushed resulting in an initial large circular shape of deformation in the center area of panels. From this moment on, the panel is starting to act as a free vibration beam with initial velocities. The deformation modes consisted of homogeneous large deformation for both face sheets, obvious deformation border on wet face sheet, core node imprinting, remarkable wrinkled skin of deformation border, and a partial delamination and partial tear failure of the dry face. The blast-resistance of sandwich panel can be highly efficiently improved by increasing the thickness of core structure.